Paraoxonase and Arylesterase Activities, Lipid Profile, and Oxidative Damage in Experimental Ischemic Colitis Model. (12th November 2012) - Unal, Ethem; Eris, Cengiz; Kaya, Bülent; Uzun, Hafize; Cavdar, Faruk; Yildar, Murat; Kiziler, Ali Riza; Aydemir, Birsen; Gunes, Pembegul; Kutanis, Riza; Titiz, Izzet
Abstract : Objective . In the present study, since PON1 is known as an HDL-associated antioxidant enzyme that inhibits the oxidative modification of LDL and oxidative stress plays a role in the pathogenesis of mesenteric ischemia, we investigated the changes in PON1 activity and lipid profile in an experimental ischemic colitis model. Methods . Forty male Wistar albino rats were divided into two groups: the control group (N = 15 ) and the experimental group (N = 25 ). All animals were anesthetized with ether and ketamine anesthesia to undergo a midline laparotomy. Ischemic colitis was induced by marginal vessel ligation in the splenic flexura (devascularization process). A sham laparotomy was performed in the control group. All animals were sacrificed on the seventh postoperative day. Oxidative stress marker (malonyldialdehyde, MDA), lipid profile, and paraoxonase (PON-1) and arylesterase activities were determined. Histopathological evaluation was done under light microscopy, after sectioning and staining with hematoxyline and eosin. Statistical analysis was conducted using Student's t -test and Mann-Whitney U test, and P < 0.05 was considered as statistically significant. Results . There was a significant decrease in both serum and tissue PON1 activity in ischemic colitis group (P < 0.01, for each). Similarly, arylesterase levels showed a parallel decrease in both tissue and serum of the experimental group (P < 0.01 and P < 0.001, retrospectively). MDA, an oxidative stress marker, was seen to increase in the experimental group (P < 0.01, tissue; P < 0.05, serum). In experimental group, there was a significant rise in serum total cholesterol and LDL levels (P < 0.001, for each). However, HDL level decreased significantly (P < 0.001 ). Triglycerides did not show any change between the groups (P > 0.05 ). Conclusions . PON1 and arylesterase play an important role in the pathophysiology of ischemic colitis.